2014
DOI: 10.1021/jp507710k
|View full text |Cite
|
Sign up to set email alerts
|

Surface Segregation and Chemical Ordering Patterns of Ag–Pd Nanoalloys: Energetic Factors, Nanoscale Effects, and Catalytic Implication

Abstract: We performed Monte Carlo simulations to determine the roles of energetic factors and nanoscale effects in the surface segregation and chemical ordering patterns of Ag-Pd nanoalloy particles.Ag atoms significantly segregate onto the surface and preferentially occupy the low-coordinated sites, which significantly reduce the surface and strain energies of the nanoalloys. The segregation isotherms reveal that surface Ag composition is enhanced with increasing particle size or Ag concentration to circumvent the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 106 publications
3
36
0
1
Order By: Relevance
“…Indeed, the surface free energy of Ag metal is lower than that of Pd metal based on calculated and experimental results from others. [35][36][37][38] Mezey 37 reported surface free energies (SFE) of 2043 and 1302 ergs cm −2 for Pd and Ag metallic surfaces at 298 K, respectively, indicating that it is thermodynamically preferred for Ag to diffuse to the surface of a Ag-Pd bimetallic particle. Tang 38 has also calculated the SFE values of specific Ag facets and estimated the free energies of the two most common facets of Ag particles, the (111) and (100) surfaces, are 881 and 948 ergs cm −2 , further showing the thermodynamic favorability for Ag diffusion to the surface of Pd-Ag bimetallic particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the surface free energy of Ag metal is lower than that of Pd metal based on calculated and experimental results from others. [35][36][37][38] Mezey 37 reported surface free energies (SFE) of 2043 and 1302 ergs cm −2 for Pd and Ag metallic surfaces at 298 K, respectively, indicating that it is thermodynamically preferred for Ag to diffuse to the surface of a Ag-Pd bimetallic particle. Tang 38 has also calculated the SFE values of specific Ag facets and estimated the free energies of the two most common facets of Ag particles, the (111) and (100) surfaces, are 881 and 948 ergs cm −2 , further showing the thermodynamic favorability for Ag diffusion to the surface of Pd-Ag bimetallic particles.…”
Section: Resultsmentioning
confidence: 99%
“…[35][36][37][38] Mezey 37 reported surface free energies (SFE) of 2043 and 1302 ergs cm −2 for Pd and Ag metallic surfaces at 298 K, respectively, indicating that it is thermodynamically preferred for Ag to diffuse to the surface of a Ag-Pd bimetallic particle. Tang 38 has also calculated the SFE values of specific Ag facets and estimated the free energies of the two most common facets of Ag particles, the (111) and (100) surfaces, are 881 and 948 ergs cm −2 , further showing the thermodynamic favorability for Ag diffusion to the surface of Pd-Ag bimetallic particles. In support of the first possibility, Xia et al 39 reported that when Na 2 PdCl 4 was added to a suspension of Ag nanocubes, etch pits developed on the surfaces of the nanocubes, primarily at the corners.…”
Section: Resultsmentioning
confidence: 99%
“…Most other approaches to specific site blocking, including those involving Pd catalysts, have employed additional metals that will hypothetically have different affinities for different surface facets 44 . Monte-Carlo and DFT calculations have demonstrated that the second metal with lower surface energy (Cu, Ag and Au) preferentially occupies the low coordination sites on Pd particle surface, such as high index planes, corners and edges [45][46][47] . In addition to simulation results, the strong tendency of Cu atoms to locate at low-coordinated surface sites was supported by low energy ion scattering spectroscopy and FTIR spectroscopy after CO adsorption on the surface; Cu addition was found to cause Pd catalyst selectivity improvement for the hydrogenation of 1,3-butadiene to butene and the dehydrogenation of ethanol to ethanal at the cost of activity 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…20 . During the optimization, the upper three layers (including the Cu 12 O 8 layer) were allowed to be relaxed and the bottom two layers of Pd were frozen 50 .…”
Section: Methodsmentioning
confidence: 99%